Penguasaan Konsep dan Sikap Ilmiah Siswa Kelas V Melalui Pembelajaran RADEC Menggunakan Zoom Meeting pada Materi Benda dan Perubahannya - Rahmafinia, Wulan; Sujana, Atep; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2021)
The background of this research is the authorâ€™s interest in mastery concepts and scientific attitudes in elementary school. However, the fact is mastery concepts and scientific attitudes of students are still very low. The application of the RADEC model in learning activities is one of the new breakthroughs that can be made in order to increasing mastery concepts and growing up scientific attitudes. RADEC learning is directing students to construct their understanding independently through learning syntaxs that must be done systematically. The purpose of this research is to know the learning process using the RADEC model, mastery concepts of students and the scientific attitudes that appear in students during the learning activities through zoom meetings. This research used descriptive qualitative method. Respondents in this study were fifth grade students of SDN Sukaraja I. This study uses concept mastering questions and observation guidelines instruments. The results showed that: (1) The process of implementing RADEC learning was very effective. (2) Concepts mastering of students has increased after doing RADEC learning where all students have mastered the concept of â€œBenda dan Perubahannyaâ€ materials. (3) The scientific attitude that appears in students is the attitude of responsibility, accuracy, curiosity, critical thinking and cooperation. The five scientific attitudes continue to increase in percentage at each stage. The implication of this research is to make a practical contribution that the application of the RADEC learning model in learning activities can improve students' mastery concepts and scientific attitudes.